From Underground to Mainstream: Establishing a Medical Lexicon for Psychedelic Therapy - Beswerchij, Andrew; Sisti, Dominic (Frontiers in Psychiatry, 2022)
We argue that nonstigmatizing and precise terminology grounded in the medical model will advance both the science and public acceptance of psychedelics. Researchers and clinicians should take care to distinguish between medical, recreational, and spiritual uses to set clear boundaries and expectations for patients. Ethically fraught or stigmatized terms should be replaced with terminology that is medically and scientifically descriptive and accurate. A medicalized linguistic framework around psychedelics will potentially yield benefits and mitigate risks. Replacing colloquial names with scientific names for medicines and therapies may help correct misconceptions about psychedelics commonly held by both professionals and the public. A harmonized medical lexicon will also provide a common language for important instances of communication—such as the informed consent process—between professionals and participants. Our recommendations draw upon communications research in addiction medicine and aim to encourage the development, acceptance, and implementation of nonstigmatizing terminology in psychedelic research and treatment.